The Pristine survey – VI. The first three years of medium-resolution follow-up spectroscopy of Pristine EMP star candidates. Issue 2 (21st September 2019) - Aguado, David S; Youakim, Kris; González Hernández, Jonay I; Allende Prieto, Carlos; Starkenburg, Else; Martin, Nicolas; Bonifacio, Piercarlo; Arentsen, Anke; Caffau, Elisabetta; Peralta de Arriba, Luis; Sestito, Federico; Garcia-Dias, Rafael; et al.
ABSTRACT: We present the results of a 3-yr long, medium-resolution spectroscopic campaign aimed at identifying very metal-poor stars from candidates selected with the CaHK, metallicity-sensitive Pristine survey. The catalogue consists of a total of 1007 stars, and includes 146 rediscoveries of metal-poor stars already presented in previous surveys, 707 new very metal-poor stars with $\rm [Fe/H] \lt -2.0$, and 95 new extremely metal-poor stars with $\rm [Fe/H] \lt -3.0$ . We provide a spectroscopic [Fe/H] for every star in the catalogue, and [C/Fe] measurements for a subset of the stars (10 per cent with $\rm [Fe/H] \lt -3$ and 24 per cent with $-3 \lt \rm [Fe/H] \lt -2$ ) for which a carbon determination is possible, contingent mainly on the carbon abundance, effective temperature and signal-to-noise ratio of the stellar spectra. We find an average carbon enhancement fraction ([C/Fe] ≥ +0.7) of 41 ± 4 per cent for stars with $-3 \lt \rm [Fe/H] \lt -2$ and 58 ± 14 per cent for stars with $\rm [Fe/H] \lt -3$, and report updated success rates for the Pristine survey of 56 per cent and 23 per cent to recover stars with $\rm [Fe/H] \lt -2.5$ and $\lt -3$, respectively. Finally, we discuss the current status of the survey and its preparation for providing targets to upcoming multi-object spectroscopic surveys such as William Herschel Telescope Enhanced Area Velocity Explorer.